Left Ventricular Transmural Gradient in Mitochondrial Respiration Is Associated with Increased Sub-Endocardium Nitric Oxide and Reactive Oxygen Species Productions - Kindo, Michel; Gerelli, Sébastien; Bouitbir, Jamal; Hoang Minh, Tam; Charles, Anne-Laure; Mazzucotelli, Jean-Philippe; Zoll, Joffrey; Piquard, François; Geny, Bernard (Frontiers in Physiology, 2016)
Objective: Left ventricle (LV) transmural gradient in mitochondrial respiration has been recently reported. However, to date, the physiological mechanisms involved in the lower endocardium mitochondrial respiration chain capacity still remain to be determined. Since, nitric oxide (NO) synthase expression in the heart has spatial heterogeneity and might impair mitochondrial function, we investigated a potential association between LV transmural NO and mitochondrial function gradient. Methods: Maximal oxidative capacity (VMax) and relative contributions of the respiratory chain complexes II, III, IV (VSucc) and IV (VTMPD), mitochondrial content (citrate synthase activity), coupling, NO (electron paramagnetic resonance), and reactive oxygen species (ROS) production (H2O2 and dihydroethidium (DHE) staining) were determined in rat sub-endocardium (Endo) and sub-epicardium (Epi). Further, the effect of a direct NO donor (MAHMA NONOate) on maximal mitochondrial respiratory rates (Vmax) was determined. Results: Mitochondrial respiratory chain activities were reduced in the Endo compared with the Epi (−16.92%; P = 0.04 for Vmax and –18.73%; P = 0.02, for Vsucc, respectively). NO production was two-fold higher in the Endo compared with the Epi (P = 0.002) and interestingly, increasing NO concentration reduced Vmax. Mitochondrial H2O2 and LV ROS productions were significantly increased in Endo compared to Epi, citrate synthase activity and mitochondrial coupling being similar in the two layers. Conclusions: LV mitochondrial respiration transmural gradient is likely related to NO and possibly ROS increased production in the sub-endocardium.